11β-Hydroxysteroid Dehydrogenases: Intracellular Gate-Keepers of Tissue Glucocorticoid Action - Chapman, Karen (American Physiological Society, 2013)
Glucocorticoid action on target tissues is determined by the density of “nuclear” receptors and intracellular metabolism by the two isozymes of 11β-hydroxysteroid dehydrogenase (11β-HSD) which catalyze interconversion of active cortisol and corticosterone with inert cortisone and 11-dehydrocorticosterone. 11β-HSD type 1, a predominant reductase in most intact cells, catalyzes the regeneration of active glucocorticoids, thus amplifying cellular action. 11β-HSD1 is widely expressed in liver, adipose tissue, muscle, pancreatic islets, adult brain, inflammatory cells, and gonads. 11β-HSD1 is selectively elevated in adipose tissue in obesity where it contributes to metabolic complications. Similarly, 11β-HSD1 is elevated in the ageing brain where it exacerbates glucocorticoid-associated cognitive decline. Deficiency or selective inhibition of 11β-HSD1 improves multiple metabolic syndrome parameters in rodent models and human clinical trials and similarly improves cognitive function with ageing. The efficacy of inhibitors in human therapy remains unclear. 11β-HSD2 is a high-affinity dehydrogenase that inactivates glucocorticoids. In the distal nephron, 11β-HSD2 ensures that only aldosterone is an agonist at mineralocorticoid receptors (MR). 11β-HSD2 inhibition or genetic deficiency causes apparent mineralocorticoid excess and hypertension due to inappropriate glucocorticoid activation of renal MR. The placenta and fetus also highly express 11β-HSD2 which, by inactivating glucocorticoids, prevents premature maturation of fetal tissues and consequent developmental “programming.” The role of 11β-HSD2 as a marker of programming is being explored. The 11β-HSDs thus illuminate the emerging biology of intracrine control, afford important insights into human pathogenesis, and offer new tissue-restricted therapeutic avenues.